PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN HANDPONE SAMSUNG (STUDI KASUS PADA PELANGGAN PONSEL BEDEPE PASIR PENGARAIAN) - Seprini., Andi Rulyadi, Arrafiqurrahman, (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
This study aims to know the brand image, purchase decisions and brand image influences on purchase decisions Mobile Samsung (Study on Mobile Subscribers BEDEPE Pasir Pengaraian). The study population is all consumer and samples taken 30 respondents and methods of sampling with accidental sampling technique. Analysis of the data using a questionnaire with Likert scale measurement and testing using simple linear regression. Based on the research results show the value of R2 = 0.923 indicates that the variation of brand image to purchasing decisions amounted to 92.30% and the remaining 7.7% is influenced by other factors not examined, such as price, product quality, promotional mix and judgments on. For the consideration for the company are Mobile Bedepe Pasir Pengaraian to notice the factors that can influence consumer decisions in the purchase of mobile phones outside of the factors in this study. Furthermore, for the company to maintain relations and cooperation built up well to every customer, especially with potential customers.